Axillary lymph node pigmentation in tattooed patients - Toshiyuki Yamaguchi (Clinical Case Reports, 2023)
Key Clinical Message Tattooed pigments often migrate to the regional lymph nodes, leading to staining and swelling of these nodes. This migration can create confusion for surgeons when evaluating regional lymph nodes for staging of malignant disease like breast cancer. Abstract A 50‐year‐old woman with left breast carcinoma underwent left mastectomy and sentinel lymph node (SLN) biopsy. A cherry blossom tattoo was observed on the left pectoral region, which she had acquired 6 years prior. Two lymph nodes were excised as SLNs and one of the two SLNs exhibited partial pink staining. Serial sections were performed on the block, revealing pinkish particles within the colored area on pathological examination. However, no metastasis was detected.